Discriminarea pe criterii lingvistice [Articol] - Săftoiu, Mihaela (CEP USM, 2023)
In any state configuration in which diversity is not accepted and equality of rights is not effectively respected and the protection measures taken by the State for the expression and development of specific identity are not effective, the phenomenon of discrimination occurs, which, in addition to the political factors involved in its emergence and development, also has psychological, social and historical factors, being a complex phenomenon. Discrimination is the different treatment of a person in connection with his or her recognition or exercise of rights because he has a characteristic or is perceived to have a specific characteristic, which may be the criterion of race, colour, nationality, ethnic origin, language, religion or belief, sex, age, disability, political opinion or membership, sexual orientation or any other similar criterion. Discrimination on the basis of language is a form of discrimination based on differences in spoken or written language, and the establishment of the minority language in a state is a first step in its analysis. Linguistic discrimination is one of the most serious forms of discrimination because it refers to the very element that connects, develops and perpetuates human communities and separates us from the animal kingdom – articulated speech.
DISCRIMINATION BASED ON LINGUISTIC CRITERIA
Keywords: linguistic discrimination; discriminarea pe criterii lingvistice; minorități